2007
DOI: 10.1177/875647930700400102
|View full text |Cite
|
Sign up to set email alerts
|

Verification and Validation Issues in a Generic Model of Electro-Optic Sensor Systems

Abstract: In general, questions of model credibility introduce more problems in a generic model than they do in models developed for one specific application since a generic formulation must allow for many applications of the model. This paper addresses the issues of model testing, verification, and validation for a generic electro-optic sensor system model. A structural approach to testing, verification, and validation is proposed that builds increasing confidence through bottomup testing, structured verification proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The distortion of the model polygon following a specifi c change in the model provides a clear indication of sensitivities and interactions, as discussed in papers by Smith et al . ( [16] and [17]). Shape-processed visualisation methods such as these lend themselves to image processing techniques for quantifi cation and a number of approaches have been considered (see [18] and [19]).…”
Section: External Validationmentioning
confidence: 98%
See 2 more Smart Citations
“…The distortion of the model polygon following a specifi c change in the model provides a clear indication of sensitivities and interactions, as discussed in papers by Smith et al . ( [16] and [17]). Shape-processed visualisation methods such as these lend themselves to image processing techniques for quantifi cation and a number of approaches have been considered (see [18] and [19]).…”
Section: External Validationmentioning
confidence: 98%
“…Polar diagrams such as these have been used successfully in the context of model testing for electro-optic sensor models ( [16] and [17]) and have been considered in the context of fault detection applications as well as in other model-testing situations ( [18] and [19]). Although they have been developed independently for model validation purposes, these diagrams have many features that are similar to those of the Kiviat diagrams ( [17] and [19]), which are applied in the software engineering fi eld for visualisation of metrics in computer software and hardware performance evaluation.…”
Section: External Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…These are very satisfactory if only one or two variables are being considered but are difficult to interpret if many variables need to be considered. In such cases a type of polar diagram (similar to the Kiviat diagrams used in software engineering for visualisation of the results of software and hardware performance evaluations) can be very helpful [5], [6], [7]. Figure 1 shows an example of this type of polar diagram, as applied to the external validation process.…”
Section: Model Quality Measures In External Validationmentioning
confidence: 99%
“…If, at any stage, it is found that the approach fails, then either a fundamental design flaw will have been exposed in the model or a limitation will have been found in the generic approach. Detailed issues of testing and validation of the generic model are discussed more extensively in an associated paper [12].…”
Section: Jdmsmentioning
confidence: 99%